Eternal Bond - Ogunbiyi, Olasunkanmi (Literamed Publications Ltd, 2003)
Kunle and helen been childhood friends and lovers but were drawn apart as a result of Helen's father's relocation from Lagos to Kano. With the passage of time, Kunle meets and falls in love with another lady, Bukky while Helen falls in love with Charles. They made plans for marriage respectively which was later called off simultaneously because they discovered they were AS genotypes...
Keywords: Plays